Neželeni učinki uporabe anaboličnih androgenih steroidov - Žvegelj, Gal (Šport (Ljubljana), 2020)
Anabolic androgenic steroids (AAS) are the most commonly used pharmacological group on the List of Prohibited Substances and Methods among elite athletes. In addition, they are also widely used by recreational athletes, adolescents and other adults. The use of AAS is associated with numerous adverse side effects, which we will address in this review paper by organ systems.
Keywords: adverse effects; anabolic androgen steroids; anabolični androgeni steroidi; antidoping; anti-doping; doping; neželeni učinki; šport; toksičnost; toxicity